Synthetic Roof Image Generation using an Extended Gaussian Mixture Model (EGMM) - Agaian, Sos S.; Rao, Shishir P.; Yeole, Rushikesh D.; Hallam, Cory R.A. (IJRDO -Journal of Computer Science Engineering, 2017)
In this paper, we address the problem of generating synthetic images by using a single image, or multiple images,and present an effective Extended Gaussian Mixture Model (EGMM). We apply this method to roof surface images forinvestigating and identifying differences, changes, and/or structural damage. This technique allows a single impression of aroof to be randomly generated according to input parameters, and can produce new image models using multiple roofimages. We further extend GMMs by mixing color textures of the roof images to generate new models. The best fit statisticalmodel image is obtained by finding the minimum pixel distances as compared to the original image. This approach generatesvery realistic roof models that are useful in performance evaluation and testing, and offers the potential for further researchand application in other surface inspection processes.